Antifungal activities of phyto extracts against major pathogens infecting oyster mushroom [Pleurotus ostreatus (Jacq.) P. Kumm] - Kotadiya, Urvashi S; Talaviya, Jayadipkumar R; Shah, KD; Lathiya, SV; Savaliya, VA (Mushroom Research, 2022)
Short communication